2017
DOI: 10.1590/s2175-97902017000116021
|View full text |Cite
|
Sign up to set email alerts
|

Quality indicators of pharmacists' services in community pharmacies in Paraná State, Brazil

Abstract: Pharmacists and their pharmacies have been evolving in their roles as health promoters in Brazil. Some examples are the recent legislation reaffirming the role of Brazilian pharmacies as health institutions, rather than having only a commercial profile, giving greater clarity to pharmacists about their roles as health care providers. This evolution came with the recognition that is already seen in other developed countries, confirming the need for the pharmacist as a health promoter, and not simply a dispenser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Most of the studies were from the UK (n=15), 15 26–30 42 54 56 65 77 90 100 106 111 USA (n=11) 41 47 51 53 64 66 68 72 81 88 98 and Australia (n=7). 45 46 49 52 59 83 113 Of the remaining studies, four each were from Japan, 57 61 62 79 the Netherlands 55 102–104 and Thailand 67 69 95 105 ; three each from Germany, 58 75 108 Estonia, 71 78 115 Iran 48 76 84 and Vietnam 93 96 97 and two each were from Lebanon, 112 114 UAE, 60 86 Brazil 107 110 and Spain. 63 73 One each from Canada, 74 Finland, 99 New Zealand, 43 Lithuania, 44 Malaysia, 87 Poland, 91 Slovenia, 80 Serbia, 70 Sudan, 94 Nigeria, 109 Iraq, 92 Pakistan 89 and China.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies were from the UK (n=15), 15 26–30 42 54 56 65 77 90 100 106 111 USA (n=11) 41 47 51 53 64 66 68 72 81 88 98 and Australia (n=7). 45 46 49 52 59 83 113 Of the remaining studies, four each were from Japan, 57 61 62 79 the Netherlands 55 102–104 and Thailand 67 69 95 105 ; three each from Germany, 58 75 108 Estonia, 71 78 115 Iran 48 76 84 and Vietnam 93 96 97 and two each were from Lebanon, 112 114 UAE, 60 86 Brazil 107 110 and Spain. 63 73 One each from Canada, 74 Finland, 99 New Zealand, 43 Lithuania, 44 Malaysia, 87 Poland, 91 Slovenia, 80 Serbia, 70 Sudan, 94 Nigeria, 109 Iraq, 92 Pakistan 89 and China.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies reported the development or assessment of quality indicators for CPs. [99][100][101][102][103][104][105][106][107][108][109][110][111] Four studies described and defined standards or guidelines for good pharmacy practice which can be used to help define quality. [112][113][114][115] Multiple methods were used including: surveys (n=46), 26 114 115 qualitative interviews (n=9), 15 30 45 49 61 69 70 73 83 focus groups, 27 53 63 77 premeasurement and postmeasurement of adherence to standards, 113 biographic and photographic techniques, 42 participant observations, 51 nominal group technique, 43 applying indicators in practice, 103 104 Q-methodology, 96 97 stakeholder event, 112 deductive content analysis, 71 patient stories 65 and mixed methods (n=4).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…We can infer that the modifications in the structure were the results of the political‐administrative interventions and had a positive influence on the work process, since the pharmacists began to have private areas in which to attend to patients, and consumables and technical procedures with which to perform CPS. These facts are reinforced by several studies that have demonstrated how the evaluation of the structure can predict the quality of services and how the structure can influence the development of the process and the achievement of favourable results by the health services 40,56,62,85‐89 . Thus, to obtain positive results in health services, health managers and professionals must have good structure and good process in the CPS implementation.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Guideline for Prevention, Detection, Evaluation and Management of Adult Hypertension, PHC to the patient by pharmacists and others professionals should be share ( 2 ) . The importance of pharmaceutical services is recognized, that allowed patients with chronic conditions and polymedicated to have access to the pharmacotherapeutic follow up ( 7 ) . In this context, monitoring polypharmacy is a primary care practice that can contribute to reduce of side effects, as well as the risks of interactions, and improve adherence.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the pharmaceutical profession underwent important transformations, with a change of roles and focus on the provision of clinical services ( 7 ) . Regulatory advances defined the pharmacy as a health entity dedicated to providing a pharmaceutical service to promote better health care for patients ( 8 ) .…”
Section: Introductionmentioning
confidence: 99%